Lignin-graphene oxide inks for 3D printing of graphitic materials with tunable density. (August 2020) - Roman, Julien; Neri, Wilfrid; Fierro, Vanessa; Celzard, Alain; Bentaleb, Ahmed; Ly, Isabelle; Zhong, Jing; Derré, Alain; Poulin, Philippe
Graphical abstract: Highlights: Unlike polymers and metals, graphite cannot be directly 3D printed. Previous attempts to print graphitic structures lead to weak and highly porous materials. Dense and robust structures can be printed using lignin and graphene oxide as precursors. Properties and density can be tuned by changing the fraction of lignin and grapheme. Abstract: Graphitic structures, unlike polymers and metals, cannot be directly printed in 3D. We demonstrate here that graphitic structures can be shaped in 3D by using direct-ink writing (DIW) of lignin-graphene oxide solutions that are then dried and carbonized. Lignin is a promising precursor for the elaboration of bio-based carbon materials because of its low cost, natural availability and high carbon content. The rheology of the inks is controlled by the presence of graphene oxide (GO) in order to make the solutions viscoelastic and printable. The GO flakes are found to align during ink extrusion. This behavior is understood by considering the applied extrusion shear stress and the yield stress of the inks. By adjusting the relative fraction of GO and lignin, it is possible to change the density, the graphitic order, and thus the electrical and mechanical properties of the printed materials. In particular, GO promotes not only graphitic order but also porosity. By contrast, high amounts of lignin allow preparing denser but less ordered carbon structures. The possibility to vary density and properties offers an opportunity for the development of graphitic 3D materials with tunable properties.